Prevalensi Infeksi Entamoeba Spp pada Ternak Babi di Pegunungan Arfak dan Lembah Baliem Provinsi Papua - Prasanjaya, Putu Nara Kusuma; Suratma, Nyoman Adi; Damriyasa, I Made (Buletin Veteriner Udayana, 2014)
Eighty percent of selected pig farm’s in two region’s in Papua Wet infected by Entamoeba spp, and also 32,4% from 102 pig’s infected by its parasite. The examined use SAF (Sodium Acetic Formaldehyde), to determine the prevalence of Entamoeba spp. The result of the study indicated of pig’s in Papua were infected by Entamoeba spp indicated that the prevalence was significatly higher in Baliem valley than Arfak Mountain.
Keywords: Prevalence of Entamoeba spp, pig, Arfak Mountain, Baliem valley